If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+9(x-9)=10-3(x-8)
We move all terms to the left:
5+9(x-9)-(10-3(x-8))=0
We multiply parentheses
9x-(10-3(x-8))-81+5=0
We calculate terms in parentheses: -(10-3(x-8)), so:We add all the numbers together, and all the variables
10-3(x-8)
determiningTheFunctionDomain -3(x-8)+10
We multiply parentheses
-3x+24+10
We add all the numbers together, and all the variables
-3x+34
Back to the equation:
-(-3x+34)
9x-(-3x+34)-76=0
We get rid of parentheses
9x+3x-34-76=0
We add all the numbers together, and all the variables
12x-110=0
We move all terms containing x to the left, all other terms to the right
12x=110
x=110/12
x=9+1/6
| x+1.5−0.5x=4.5 | | 5x3-12x-16=0 | | x/2-3=3/4 | | 5-(8x+5)=3-x | | −2z+10+7z=16z+7 | | w-12=8.3 | | 4/3z+2=26 | | 5x^2+5=6x | | 3(y+3)/5=+2y+6 | | 15.24+0.06(x+3)=15.99-0.11 | | 3x+50.4=3.6(x+12.6) | | w-17=3.6 | | k-8=36 | | F(x)=8-3x^2x=3 | | 1/6n+8=2 | | 25-(x+7-(9x-2)=0 | | -3t^2-12t+6=0 | | 3.8+10m=6.96 | | 110x+.50=30x+.60 | | 25-(x+7=9x-2 | | x+3=2x-21 | | 4(8n−1)=19+32n | | +x/3+x/4+x/5=100 | | -32=4x-9 | | -(4y+3)-(-3y-4)=-6 | | 44/176=16r+1/176 | | 4(8n−1)=19+32n4(8n−1)=19+32n | | -10-x/3=12 | | |x+2|-3=11 | | 5x-(x+1)^2+(2x-1)^2=2-(x+3)*(x-2) | | 0.40x+0.06(30)=98 | | 33/27=11/x |